A transnational perspective on the evolution of the synthetic cannabinoid receptor agonists market: Comparing prison and general populations. Issue 4 (28th January 2021) - Norman, Caitlyn; Halter, Sebastian; Haschimi, Belal; Acreman, Dean; Smith, Josie; Krotulski, Alex J.; Mohr, Amanda L.A.; Logan, Barry K.; NicDaéid, Niamh; Auwärter, Volker; McKenzie, Craig
Abstract: The synthetic cannabinoid receptor agonist (SCRA) market is transnational, and the availability of individual SCRAs changes regularly in response to national and international legislative controls. This generates a cyclic pattern and near constant evolution of SCRA compounds. This study reports toxicology‐based and/or seized sample‐based prevalence data relating to SCRA use in prisons from Germany, the United Kingdom (UK; Scotland and Wales), and the United States (US), representing 4427 individual test results. The study examines SCRA detections in prisons from July 2018 to September 2020, and where possible, prison‐based data are compared with SCRA prevalence data in the wider population. The relative influence of Chinese, other international, and national drug legislation on the prevalence of individual SCRAs in prisons is also considered. tert ‐Leucinate‐ and valinate‐indole‐ and indazole‐3‐carboxamides were the most common SCRA detections, and MDMB‐4en‐PINACA was one of the most commonly detected SCRAs in all jurisdictions by September 2020. However, despite there being a global production and supply market, there were notable regional differences. Analog controls in German and US legislation may have led to increased compound diversity that is not reflected in the UK which has both analog controls and a blanket ban on psychoactive substances. While there were regional differences, SCRA prevalence in prisons closely aligned with the SCRAs detected on the local market, demonstrating that SCRA (and possibly other NPS) monitoring programs in prisons can act as early warning systems for the wider population in that given jurisdiction. Abstract : This study reports prevalence data relating to synthetic cannabinoid receptor agonist (SCRA) use in prisons in Germany, the United Kingdom (Scotland and Wales), and the United States. The emergence of prevalent SCRAs is very similar across all jurisdictions, although the analog controls in German and US legislation may have led to increased compound diversity that is not reflected in the United Kingdom which has a blanket ban on psychoactive substances. SCRA prevalence in prisons was found to closely align with the SCRAs detected on the local market.